2018
DOI: 10.17159/2519-0105/2018/v73no5a1
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood caries experience of children accessing selected immunization facilities in Johannesburg

Abstract: introduction: Despite notable achievements in the enhancement of the oral health of populations globally, early childhood caries (ECC) remains a common condition, particularly in developing countries. Mother and child oral health programs at immunization facilities were piloted in two Gauteng Districts in 2015 in order to address the burden of disease. Hence there was an opportunity to assess the ECC experience and risk factors contributing to ECC at these sites. Methods: This retrospective study included reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Mohamed and Barnes [ 34 ] found that parents of children had jobs that did not require a tertiary education. In addition, Molete and Phakela [ 25 ] found that most caregivers had a high school education. The results were supported by Ntombela and Mndzebele [ 30 ] who found a caries prevalence of almost 60%, where 90% of the caregivers had a primary school education.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mohamed and Barnes [ 34 ] found that parents of children had jobs that did not require a tertiary education. In addition, Molete and Phakela [ 25 ] found that most caregivers had a high school education. The results were supported by Ntombela and Mndzebele [ 30 ] who found a caries prevalence of almost 60%, where 90% of the caregivers had a primary school education.…”
Section: Resultsmentioning
confidence: 99%
“…There was no difference in caries prevalence in children whose households had garbage collection or no garbage collection [ 21 ]. Overall, urban children appear to have a higher prevalence, dmft and sugar intake than rural children [ 7 , 23 , 25 , 27 29 , 37 – 39 ]. However, rural children had a higher plaque index [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…[9,10] During the evaluation of 10 schools-based oral health programmes in the District of Tshwane, the complexities and challenges that oral health providers experience while attempting to implement preventative policy objectives became apparent. The preliminary findings of the analysis revealed that none of the 10 schools evaluated managed to achieve even an acceptable level of adherence (50%) to policy (Molete et al, 2018).…”
Section: Editorialmentioning
confidence: 95%
“…Challenges that were observed and reported include issues of having to provide school oral health programmes and services without chairside assistance, due to staff shortages. Other factors included defective portable equipment, ill-equipped school facilities, inadequate teacher co-operation and lack of school health-promotion policies addressing sugary snack intake (Molete et al, 2018).…”
Section: Editorialmentioning
confidence: 99%
See 1 more Smart Citation